Study of Optimal Deposition Conditions for an Inductively Coupled Plasma Chemical Vapour Deposition (ICP-CVD) System - Zhang, Haiqiang (My University, 2005)
High-density plasma technology is becoming increasingly attractive for the deposition of dielectric films such as silicon dioxide, silicon nitride and silicon oxynitride. In particular, inductively coupled plasma chemical vapor deposition (ICP-CVD) offers several technological advantages for low temperature processing over other plasma-enhanced chemical vapor deposition (PECVD), such as higher plasma density, lower hydrogen content films, and lower cost. A new ICP-CVD system has been set up at McMaster University.
The project focused on the calibration of this system and the establishment of its performance characteristics. A combination of 0 2/ Ar/SiH4 gases was used to deposit Si02 thin films on single-crystal Si wafers under various conditions. Substrate temperatures were calibrated from 200 to 400°C, and were found to linearly relate to heater temperatures. Calibration of the minimum reflected power showed that the ICP source is efficient to generate a stable plasma for 02, N2 and Ar gases within a wide range of flow rates from 3 to 1 OOsccm, while the reflected power remains below 10 Watts. Uniformity was found to be sensitive to many factors. Under optimal conditions, uniformity could be controlled better than 1% with a good shape of thickness distribution. The refractive indexes of the deposited films were measured with ellipsometry and showed an inverse relation with the ratio of oxygen to silane flow rate.
Keywords: deposition; plasma; chemical vapour; dielectric films